2014
DOI: 10.3390/s141120480
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SnO2|WO3 Heterocontact Properties during the Detection of Hydrogen Sulphide

Abstract: The main objective of the paper was the analysis of the properties of SnO2|WO3 heterocontact as well as the determination of its response to 50 ppm of hydrogen sulphide. It was noticed that the sensitivity of the sensor being tested to hydrogen sulphide depended significantly on the polarization direction. When its parameters were compared with those of sensors the gas-sensitive layer of which was made only from one type of metal oxide, a high impact of the heterocontact on the electric charge transport was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In the steady state condition, the formation of an electron-enriched zone at the tin dioxide side of the interface enhances oxygen adsorption in this region [18,41]. Additionally, it leads to a more substantial depletion of titanium dioxide grains and formation of contact potential at the SnO 2 /TiO 2 boundary.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the steady state condition, the formation of an electron-enriched zone at the tin dioxide side of the interface enhances oxygen adsorption in this region [18,41]. Additionally, it leads to a more substantial depletion of titanium dioxide grains and formation of contact potential at the SnO 2 /TiO 2 boundary.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that grain boundaries between different oxides have higher catalytic activity, compared to single-oxide grain boundaries [13,14,15,16,17]. Recently, SnO 2 -based metal oxide structures with n-p and n-n heterojunction have attracted a great deal of interest as gas sensing materials [2,13,14,15,16,17,18,19]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electric measurements were carried out at a test stand comprising a HP E3632 A power supply unit type (Agilent Technologies Inc., Santa Clara, CA, USA), a Keithley 2400 current–voltage source, the measurement chamber and a PC provided with appropriate software. Current-voltage characteristics of sensors at various temperatures were recorded using an potentiostat-galvanostat type SI 1287 from Solartron Analytical (Farnborough, UK), with the use of the CorrWare software from Scribner Associates Inc. (Southern Pines, NC, USA) [15]. …”
Section: Methodsmentioning
confidence: 99%
“…1). The reactions of adsorption of O 2 and diethyl ether during this process may be described as follows [36]:…”
Section: In-situ Drft-ir Studymentioning
confidence: 99%